SHRIMP U-Pb zircon ages of granitoids in the Wulashan gold deposit, Inner Mongolia, China: Timing of mineralization and tectonic implications. - Miao, L.; Qiu, Y.; McNaughton, Neal; Fan, W.; Groves, D.; Zhai, M. (Bellwether Publishing, 2003)
The Wulashan gold deposit, situated along the northwestern margin of the North China craton (NCC), is hosted by ductile-brittle faults within Archean metamorphic volcano-sedimentary rocks of the Wulashan Group. This deposit is characterized by gold-bearing quartz-K feldspar and quartz veins. Both granitoid batholiths and pegmatite dikes intruded the metamorphic basement rocks, and are spatially associated with gold mineralization. Contrasting genetic models have been proposed for the deposit due to lack of reliable age data. Our new SHRIMP U-Pb zircon ages for these intrusions now reveal important constraints on the mineralization time and tectonic evolution of this region. These intrusions contain inherited zircons of about 2.55 Ga, probably from the Wulashan basement that was intruded by pegmatite dikes at about 1.84 Ga; the latter probably are related to the major tectonic event leading to the final amalgamation of the NCC. The basement subsequently underwent at least three tectono-thermal events during Phanerozoic time (at 353 ± 7, 169 ± 7, and 132 ± 2 Ma).Combined with previous Ar-Ar and K-Ar ages, we suggest two gold mineralization episodes for the Wulashan gold deposit. The first episode occurred at about 350 Ma, indicated by ages of a goldrelated fuchsite and the Dahuabei granitoid batholith. This supports a previously proposed model that relates gold mineralization to the Dahuabei granite that formed during collision of the Paleo-Mongolian block with the NCC. The second one occurred in the late Yanshanian period, as indicated by the mineralized K-feldspar-rich vein of 132 ± 2 Ma. This episode is simultaneous with those in the eastern NCC, indicative of a widespread late Yanshanian metallogenic event that was a response either to the subduction of the Izanagi-Pacific plate beneath eastern China or to the removal of the Early Cretaceous lithosphere in the eastern NCC.